Risk Evaluation of a Boron Mine and Processing Plant with Respect to Dust - Hasbi Atılmış; Baran Tufan (Archives of Current Research International, 2019)
The technological developments affect mining sector directly since the machineries and equipment used in this sector changes along with constantly developing technology. So, the risks of occupational accidents and occupational diseases are quite high in this sector. It is necessary to focus on occupational health and safety in the mining sector regarding the machineries and equipment used. This study was carried out in an open pit mine of boron minerals with class of very dangerous in the scope of occupational health and safety. The workplace on scope is evaluated in terms of the health and safety risks of employees. In this context, one of the major types of risk is dust, originated from machineries and equipment. The stages of open pit operation, crushing, screening, grinding and bagging are evaluated regarding dust formation and control. Risks that may arise due to the use of equipment and preventative measures have been determined. Such studies impose great affect in the development of occupational health and safety with the developing mining sector and prevention of accidents that may occur.